Public Law and Order: The Eurasian Dimension - S. A. Agamagomedova (Евразийская интеграция: экономика, право, политика, 2025)
Aim and tasks. The objective of the study is to substantiate the concept and structure of public law and order in the context of Eurasian economic integration.   The objectives of the study are: review and analysis of the concepts of public law and order in the contractual and legal framework of the Eurasian Economic Union; identification of approaches to understanding public law and order; determination of its structure in the context of integration.   Methods. The following methods were used: institutional analysis, comparative analysis, system analysis — to substantiate the concept of public law and order from the point of view of integration. The method of formal logical analysis was also used — when clarifying the concept of public law and order in various acts of the integration level.   Results. Firstly, the mutual influence of the existing theory of public law and order on management processes in the context of Eurasian economic integration is highlighted. Secondly, amendments to the Constitution of the Russian Federation also contributed to the constitutionaliza tion of public law and order in Russia. Thirdly, within the framework of the integration agenda, there are processes of expansion of the traditional approach to international private law, based on the “public order clause” as a basis for refusing to comply with the requirements of international treaties and other acts, due to the differentiation of its levels and elements, the allocation of the public legal order of the integration member state and the integration entity itself.   Conclusions. The concept of public legal order in the context of the development of integration processes is acquiring a qualitatively new meaning. In addition to the fact that approaches to its understanding are significantly expanding, in relation to the Eurasian Economic Union it is possible to distinguish at least two levels of such understanding: the public legal order of the EAEU member states and the Eurasian public legal order. At the same time, the formation of the new content of the concept of public legal order in the context of Eurasian integration is influenced not only by the contractual and legal framework of the EAEU, but also by the practice of the EAEU Court.